Motivasi Tokoh Kagami Taiga Menjadi Pemain Basket dalam Manga Kuroko No Basuke Karya Tadatoshi Fujimaki - Hery Kusumajaya, Made; Ari Sulatri, Ni Luh Putu; Andry Anita Dewi, Ni Made (Humanis; Vol 21 No 1 (2017), 2017)
The research is titled "Motivation of Kagami Taiga Being a Basketball Player In Manga Kuroko no Basuke created by Tadatoshi Fujimaki". The formulation of the problem in this study examines the motivation and efforts of Kagami Taiga character to realize his dream of becoming a famous basketball player. The theory used in this research is the theory of literary psychology and motivation theory by Petri (in Risnawita, 2010: 83-85).         Data collection method used is literature study method with note technique. Data analysis method used is qualitative method with qualitative technique. Method of presentation of data analysis result is informal method. The results of this study indicate that the motivation of the character Kagami Taiga become famous basketball players can be divided into two, namely intrinsic motivation and extrinsic motivation. His intrinsic motivation is his love of basketball, his confidence in his abilities, and the desire to show basketball skills. Extrinsic motivation is the encouragement of his friends who emerged when a friendship relationship in playing basketball (peer group). The effort by Kagami Taiga to be a famous basketball player is to become a core member of the team, winning match training, winning matches, and trying to win the final.